Qualitative analysis for demand response impact on distribution system rates (2017)
(Eng) Electric power systems are subject to high electricity demand variations during short periods due to consumption habits of end-users. In these periods, the operation of distribution networks is expensive, energy losses are increased and voltages may drop for buses located far from feeders. These negative effects can be avoided when Demand Response (DR) schemes are considered. Currently, policies for promoting DR in Colombia rise and it is fundamental the establishment of criteria for identifying the impact of DR in Colombian electricity market. This work tends to classify and identify the impact of DR on Usage Costs of Distribution Systems. Based on the current rate scheme, results show that this impact can be classified in five aspects: equipment capacity, energy sales, energy losses, payments between network operators and energy service quality. Finally, parameters of current methodology for the calculation of Usage Costs that are sensitive to DR are identified and classified.